Diversity management - evolution of concepts - Žagar, Mitja (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2007)
The article presents the concept, work and development of the International Colloquium on Ethnicity: Conflict and Cooperation and its Constitutional Network that connected worldwide scholars and institutions studying international, constitutional, legal and political regulation and management of diversity and ethnic relations. Among their activities, the series of international scholarly conferences on international, constitutional, legal and political regulation and management of ethnic relations and conflicts at the end of the twentieth and the beginning of the twenty-first century contributed to the development and transformation of the field of diversity management and within it the prevention, management and/or resolution of crises and conflicts. This field underwent a dynamic development that transformed the conflict management and conflict resolution as two initially opposing and incompatible concepts and approaches to conflict into diversity management, of which an important component is the prevention, management and resolution of crises and conflicts that in an innovative way combines approaches of conflict management and conflict resolution. Successful diversity management requires a global (long-term) strategy that includes education and training as its important contents and dimension. Education and training are life-long (learning) processes that shall in formal and informal programs and frameworks include all individuals and distinct communities in a pluralist and asymmetrical society. Their key functions are preparing and enabling every individual, distinct community and diverse society for a successful coexistence, work and life in a pluralist, diverse and asymmetrical environment, developing their knowledge and skills important for peaceful and democratic management of diversity and, especially, democratic and peaceful prevention, management and resolution of crises and conflicts.
Keywords: etnični odnosi; etničnost; različnost; upravljanje različnosti; reševanje konfliktov; mirovne študije; vseživljensko učenje; državljanska vzgoja